A framework for key factors affecting compliance with self-help housing standards in Bauchi - Abubakar, Muhammad (2019)
Self-help housing as a means of housing supply to meet the ever increasing housing demand, due to the drastic failure of the public housing in the developing countries, has been on top of global debates. Recent researches pointed out the rapid increase of self-help houses in Bauchi with more than 50% against public houses since 1970s, however, with an alarming rate of increase between 2000 and 2017. The aim of this research is to determine the mediating effect of compliance intention between the factors of compliance and compliance ability and propose a conceptual model for solving the problem of noncompliance with HDS in Bauchi metropolis, Nigeria. Four research objectives were used. Further, 357 questionnaires were distributed to the housing owners, that is, individual developers in Bauchi metropolis using stratified and systematic sampling. The reliability and EFA were conducted using SPSS version 23. While the unidimensionality and mediation analysis were achieved using Amos Graphics version 23. In the first objective, the results revealed the more reliable and valid factors of compliance, these include finance, public awareness and household size. The factor loadings ranges between 0.5 to 0.9, Cronbach’s alpha ranges from 0.7 to 0.8. While CR and AVE values are 0.7 and 0.5 respectively. In objective two, the results showed that finance and public awareness have a significant direct effect on compliance ability, however, household size has no significant direct effect on compliance ability. In objective three, the results showed that compliance intention fully mediates the effect between finance and compliance ability, compliance intention also fully mediates the effect between public awareness and compliance ability. The most significant contribution of this research is the introduction of compliance intention as a good mediator among the factors of compliance, using a psychological theory of planned behavior. It also proposes a conceptual model that identifies the relationship of the key factors which contribute to compliance with HDS.